Constraints Perceived by Farmers in Commercial Goat Farming System in Tamil Nadu, India - M. Gunaseelan; B.P. Singh (Indian Journal of Extension Education, 2018)
A study was undertaken to analyze the constraints perceived by commercial goat farmers of Tamil Nadu. A sample of 120 commercial goat farmers (20 farmers from each selected districts) from 6 districts of Tamil Nadu was selected randomly for the study. The results of study revealed that marketing (71.02%) was the main significant constraint followed by socio-economic (62.63%), management (62.04%), technological (60.33%) and institutional (58.99%) constraints as perceived by commercial goat farmers. The important socio economic constraints were high cost involved in construction of slatted floor housing (70.58%) and higher capital investment (70.25%). With regard to technological constraints, the vital constraints were non-availability of high-yielding breeding stock (66.33%) and non-availability of balanced feed (64.95). In respect of institutional constraints, limited veterinary infrastructure and services (68.67%) and lack of training on scientific goat farming (59.79%) were the significant constraints. The major management constraints were inadequate feed and fodder resources (68.85%) and insufficient knowledge about scientific goat production and management (65.87%). With respect to marketing constraints, lack of organised goat market (79.00%) and price regulating agency (78.10%) were major significant constraints in commercialization of goat production.